THEORETICAL ASPECTS OF STUDYING CONTINUOUS PROFESSIONAL SELF-DEVELOPMENT OF PRIMARY SCHOOL TEACHERS - Сидоренко, Юлія (SWorldJournal, 2025)
The relevance of the study is determined by the large-scale transformational processes in society and the need to develop a modern, competitive teacher capable of continuous professional self-development. Special attention is paid to the training and ret